2013
DOI: 10.1186/1471-2458-13-580
|View full text |Cite
|
Sign up to set email alerts
|

Influence of socioeconomic and demographic status on spirometry testing in patients initiating medication targeting obstructive lung disease: a population-based cohort study

Abstract: BackgroundSocioeconomic status is known to influence the prevalence, severity and mortality of obstructive lung diseases, but it is uncertain whether it affects the use of diagnostic spirometry in patients initiating treatment for these conditions. The objective of this paper was to examine a possible association between education, income, labour market affiliation, cohabitation status and having spirometry performed when initiating medication targeting obstructive pulmonary disease.MethodsWe conducted a popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…This contrasts with a UK study showing lower use of spirometry among socioeconomically deprived patients, 18 and in part with a Danish study that found lower use of spirometry among patients with the highest level of education. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts with a UK study showing lower use of spirometry among socioeconomically deprived patients, 18 and in part with a Danish study that found lower use of spirometry among patients with the highest level of education. 19 …”
Section: Discussionmentioning
confidence: 99%
“… 13 Lower socioeconomic status (SES) has also been found to be associated with reduced health-care access, infrequent monitoring with spirometry and worsening of the prognosis of COPD. 11 , 18–20 …”
Section: Introductionmentioning
confidence: 99%
“…Seeking medical help is a complex process, shaped by demographic, structural and individual factors such as age, sex, access to healthcare, socioeconomic inequalities, cultural norms, gender roles and education. 7–10 Most quantitative research documenting patterns in primary healthcare use is based on cross-sectional analysis of aggregate-level data. These findings have consistently shown that women use primary healthcare services more often than same-aged men—even when excluding consultations for childbearing and birth control.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated associations between specific practice and patient characteristics, and spirometry testing, 21 , 22 , 29 and these factors were adjusted for in the analyses. Practice characteristics comprised: GPs’ age and sex, status as training practice (yes/no), and task delegation to practice staff.…”
Section: Methodsmentioning
confidence: 99%
“… 21 Many patients who redeem first-time prescriptions for medication to treat obstructive lung diseases do not undergo spirometry testing 22 and, in recent years, a general underutilisation of spirometry in the diagnosis of both asthma and COPD has been a consistent finding across countries. 23 28 Variation has, to some degree, been explained by patient factors 29 and organisational characteristics of the practices. 21 However, considerable variation remains unexplained.…”
Section: Introductionmentioning
confidence: 99%